Intraoperative diagnostic concordance of two quantitative methods of need for orthodontic treatment in children - Berenice Olivera, Paola (2020)
Objective. The objective of this study was to evaluate the intraoperative diagnostic concordance, applying two quantitative methods such as the dental aesthetic index and the orthodontic treatment needs index in children with mixed dentition. Methods. A cross-sectional correlational observational study was carried out, with a selected sample of 20 patients who attended for comprehensive care on the Comprehensive Child and Adolescent Care Module of FOUNNE. The variables included in both indices were measured in a first measurement on the same patients, and then a second measurement was performed with a time difference of 15 days, to evaluate the intraoperative diagnostic concordance and to avoid bias due to memory. Results. A Spearman correlation analysis was performed, finding for the IONT a coefficient r=1 indicating a perfect correlation and for the DAI a r=0.99, both significant. Conclusions. A correct intraoperative diagnostic concordance of the need for orthodontic treatment was verified in the application of two quantitative methods, the dental aesthetic index and the treatment necessity index, on the same children with mixed dentition.